Legal Certainty Regarding the Employment Period of Foreign Workers in Indonesia - Komang Anggie Trisna Yunita (Jurnal Hukum Prasada, 2026)
The use of foreign workers in Indonesia is expected to improve the quality of Indonesian workers, but in reality, the number of foreign workers entering Indonesia has actually reduced job opportunities for Indonesian workers. Inconsistent regulations have caused violations in the use of foreign workers, particularly regarding the duration of foreign worker employment, which is currently contradictory. PP 34/2021 limits the extension period for foreign workers in Indonesia to a maximum of 2 (two) years and a maximum of 5 (five) years for foreign workers in Special Economic Zones. However, Minister of Manpower Regulation No. 8/2021 stipulates something different, namely that the extension of the use of foreign workers can be extended in accordance with immigration laws and regulations. This study aims to provide legal certainty regarding which regulations should be applied to determine the length of employment for foreign workers in Indonesia. This study uses a normative legal research method with a regulatory approach and a conceptual approach. The results of this study indicate that regulations that are in conflict with norms must be harmonized. Based on the theory of normative hierarchy and the principle of preference, the regulation that should be enforced is that stipulated in PP 34/2021, so that the time limit for the extension of the use of foreign workers is a maximum of 2 years and a maximum of 5 years for foreign workers in special economic zones.